The Design of The Drainage Channel for District V Penfui Timur Village - Azarya Bees; Arsenius A.L. Fuamuni; Ricardo da Rosa Soares; Dodelio De Carvalho Xavier (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
The planning of drainage channels for the people of District V of Penfui Timur Village is considered important in order to support built facilities such as roads and housing areas so that they are free from inundation when there is high intensity of rainfall. Therefore, through the International Thematic KKN activities by the Faculty of Engineering, Widya Mandira Catholic University and the Dili Institute of Technology, students and lecturers collaborated to design drainage channels for asphalt roads and dirt roads in District V, Penfui Timur Village. The results of the analysis shows that asphalt roads with a return period of 2 years require for a channel width (B) of 40 cm and for a depth (y) of 20 cm, while for a return period of 5 years requires for a channel width (B) of 46 cm and for a depth ( y) channel of 25 cm. In the other hand, for a dirt road with a return period of 2 years requires for a channel width (B) of 41 cm and for a channel depth (y) of 21 cm, while for a return period of 5 years requires for a channel width (B) of 46 cm and for a channel depth (y) of 23cm.